2008
DOI: 10.1596/1813-9450-4761
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Markets, Institutions, Policies, And Research

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 208 publications
(152 reference statements)
0
5
0
Order By: Relevance
“…Such a system may find greater acceptance and application given that it can reduce the long-term burden associated with anaerobic landfills (postclosure maintenance). In fact, under the clean development mechanism (CDM) initiative (Larson et al, 2008), landfill gas and waste management projects were a primary CDM target and gained 11% of the CDM market share in 2009 (Kossoy and Ambrosi, 2010). In fact, aerobic bioreactors aim at increasing CO 2 production at the expense of CH 4 , which has received attention as a significant contributor to global warming with CH 4 concentrations having more than doubled during the past 100 years and continue to rise with landfills being amongst the largest anthropogenic sources (Mackie and Cooper, 2009) contributing up to 30% of total CH 4 emissions (Abichou et al, 2006;Borjesson et al, 2000;Ishigaki et al, 2005;Spokas et al, 2003;).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a system may find greater acceptance and application given that it can reduce the long-term burden associated with anaerobic landfills (postclosure maintenance). In fact, under the clean development mechanism (CDM) initiative (Larson et al, 2008), landfill gas and waste management projects were a primary CDM target and gained 11% of the CDM market share in 2009 (Kossoy and Ambrosi, 2010). In fact, aerobic bioreactors aim at increasing CO 2 production at the expense of CH 4 , which has received attention as a significant contributor to global warming with CH 4 concentrations having more than doubled during the past 100 years and continue to rise with landfills being amongst the largest anthropogenic sources (Mackie and Cooper, 2009) contributing up to 30% of total CH 4 emissions (Abichou et al, 2006;Borjesson et al, 2000;Ishigaki et al, 2005;Spokas et al, 2003;).…”
Section: Discussionmentioning
confidence: 99%
“…The economic viability of the latter is questionable, particularly for small landfills and in developing countries where highly degradable food waste constitutes 60-80% of the waste stream (El-Fadel and Khoury, 2001). In fact, under the clean development mechanism (CDM) initiative (Larson et al, 2008), landfill gas and waste management projects were a primary CDM target and gained 11% of the CDM market share in 2009 (Kossoy and Ambrosi, 2010). However, reviews of project reports for the same period (Ballik, 2009;Peterson et al, 2009;Unnikrishnan and Singh, 2010) revealed that LFG projects have failed to deliver the targeted emission reductions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, markets are being set up directly as an instrument for different environmental issues (for an overview, see Larson, Ambrosi, Dinar, Rahman, & Entler, 2008). They have, for example, successfully been employed in sustainable fishery (Anderson & Sutinen, 2006;R.…”
Section: Governance and The Use Of Market Instrumentsmentioning
confidence: 99%
“…Linking the CDM to the EU ETS, a cap-and-trade system, was not foreseen when the mechanism was designed, but it has increased the general liquidity and demand for carbon credits in the market. Furthermore, the CDM has initiated environmental technology transfers (for a good overview, see Benecke, 2009;Dechezlepetre, Yann, & Yann, 2008;Larson et al, 2008). As our case studies will show in more detail, the latter has essentially been achieved through capacity development, such as skills development and administrative strengthening.…”
mentioning
confidence: 99%
“…The creation of carbon funds works in promoting climate change awareness, promotion of green investments and reducing transaction costs associated with dealing with greenhouse gas emissions. However planned green project investments still remain much more than the governments and development institutions can finance (Larson, Ambrosi, Dinar, Rahman, & Entler, 2008). This therefore requires the active participation of the private sector which may be in surplus financial positions.…”
Section: Green Financementioning
confidence: 99%